Outcome after transcatheter occlusion of patent ductus arteriosus in infants less than 6 kg: A national study from United Kingdom and Ireland. Issue 7 (11th August 2017) - Kang, Sok‐Leng; Jivanji, Salim; Mehta, Chetan; Tometzki, Andrew J.; Derrick, Graham; Yates, Robert; Khambadkone, Sachin; de Giovanni, Joseph; Stumper, Oliver; Dhillon, Rami; Bhole, Vinay; Slavik, Zdenek; et al.
Abstract: Objectives: This study aimed to report our national experience with transcatheter patent ductus arteriosus (PDA) occlusion in infants weighing <6 kg. Background: The technique of transcatheter PDA closure has evolved in the past two decades and is increasingly used in smaller patients but data on safety and efficacy are limited. Methods: Patients weighing < 6 kg in whom transcatheter PDA occlusion was attempted in 13 tertiary paediatric cardiology units in the United Kingdom and Ireland were retrospectively analyzed to review the outcome and complications. Results: A total of 408 patients underwent attempted transcatheter PDA closure between January 2004 and December 2014. The mean weight at catheterization was 4.9 ± 1.0 kg and mean age was 5.7 ± 3.0 months. Successful device implantation was achieved in 374 (92%) patients without major complication and of these, complete occlusion was achieved in 356 (95%) patients at last available follow‐up. Device embolization occurred in 20 cases (5%). The incidence of device related obstruction to the left pulmonary artery or aorta and access related peripheral vascular injury were low. There were no deaths related to the procedure. Conclusions: Transcatheter closure of PDA can be accomplished in selected infants weighing <6 kg despite the manufacturer's recommended weight limit of 6 kg for most ductal occluders. The embolization rate is higher than previously reported in larger patients. Retrievability of the occluder and duct morphology needs careful consideration before deciding whether surgical ligation or transcatheter therapy is the better treatment option.